2022
DOI: 10.1039/d2cc01404a
|View full text |Cite
|
Sign up to set email alerts
|

TfOH-catalyzed regioselective N2-alkylation of indazoles with diazo compounds

Abstract: Selective alkylation of indazoles is still a highly challenging topic in chemistry and synthesis of important molecules. Herein, a novel highly selective N2-alkylation of indazoles with diazo compounds is described...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…In fact, we recently demonstrated the regioselective N 2 -alkylation of indazoles in high regioselectivity by employing inexpensive TfOH as catalyst. 13 This example reveals that Brønsted acids as catalysts in carbene transfer contribute to overcoming the challenge of selective alkylation. With this strategy in mind, we here wish to report our new discovery that TfOH-catalyzed regioselective O -alkylation of 2-pyridones with diazo compounds has been developed (Scheme 2D).…”
mentioning
confidence: 97%
“…In fact, we recently demonstrated the regioselective N 2 -alkylation of indazoles in high regioselectivity by employing inexpensive TfOH as catalyst. 13 This example reveals that Brønsted acids as catalysts in carbene transfer contribute to overcoming the challenge of selective alkylation. With this strategy in mind, we here wish to report our new discovery that TfOH-catalyzed regioselective O -alkylation of 2-pyridones with diazo compounds has been developed (Scheme 2D).…”
mentioning
confidence: 97%
“…Indazoles are important building blocks found in various pharmaceuticals and biologically important molecules due to their biological and chemical activities. Given their importance as privileged scaffolds in medicinal chemistry, diversely substituted indazole derivatives with different functional groups have received significant attention in recent years, and a large number of synthetic methodologies available in the literature for the functionalization of indazoles have been extensively studied. The alkylation of indazoles represents one of the most efficient methods in terms of atom- and step-economy. , The transition metal catalyst has been designed as an effective tool for controllable selective functionalization in the alkylation of indazoles. Previous findings have shown that both rhodium and palladium could promote the coupling of N-substituted indazole with allenes for the synthesis of medicinally important targets. , However, due to the competitive nucleophilic sites between the N 1 and N 2 of indazoles, a mixture of N 1 - or N 2 -isomers is delivered normally under basic conditions. , Despite the fact that significant advances have been achieved in these pioneering works, the discovery of efficient catalysis for the selective N-allylation of indazoles is very limited. , Therefore, understanding how to obtain the desired product by regulating the competition for nucleophilic sites between the N 1 and N 2 positions of indazole is crucial for its development in this field. ,, …”
Section: Introductionmentioning
confidence: 99%
“…7 Chen's group reported the TfOH catalyzed regioselective N 2 -alkylation of indazoles with diazo compounds. 8 Frustrated Lewis pair (FLP) chemistry has emerged as an alternative to transition metal catalysts and has been widely applied in organic transformations. In the case of diazomethane reactions, 9 while early reports exploited the insertion of diazomethanes into B-C bonds as a route to new boranes, 10 Melen's group described B(C 6 F 5 ) 3 -catalyzed stereoselective C-H insertion, cyclopropanation, and ring-opening reactions with a variety of heterocycles.…”
Section: Introductionmentioning
confidence: 99%
“…7 Chen's group reported the TfOH catalyzed regioselective N 2 -alkylation of indazoles with diazo compounds. 8…”
Section: Introductionmentioning
confidence: 99%